Small extracellular vesicles secreted by vaginal fibroblasts exert inhibitory effect in female stress urinary incontinence through regulating the function of fibroblasts. - Xiaoyan Sun; Huimin Zhu; Wenjuan Li; Li Zhao; Wenhua Li; Xiaoyong Li; Zhenwei Xie (PLoS ONE)
Stress urinary incontinence (SUI) is a common condition in women and associated with extra-cellular matrix (ECM) reconstruction, which is mainly regulated by fibroblasts. However, the underlying mechanism remains obscure. Small extracellular vesicles (sEVs) play fundamental biological roles in various cellular functions. Some studies suggested that the sEVs were involved in the metabolism of ECM and the function of fibroblasts. The purpose of our study was to investigate the effect of sEVs secreted by vaginal fibroblasts on the pathogenesis of SUI. We showed that the fibroblasts of female anterior vaginal wall secreted sEVs. Moreover, fibroblasts of females with SUI had significantly elevated secretion of sEVs. The collagen contents, proliferation and migration capacity of fibroblasts were decreased when fibroblasts were co-cultured with fibroblasts-derived sEVs (fibroblast-sEVs) from SUI patients. Proteomic analysis revealed that fibroblast-sEVs contained various differentially expressed proteins including TIMP2, TGF-β and ABCC4, which were involved in signaling pathways of fibroblasts regulation. Therefore, we suggested that fibroblast-sEVs contributed to the pathogenesis of SUI through various proteins including TIMP2, TGF-β and ABCC4.